PENGARUH RETURN ON ASSET (ROA), RETURN ON EQUITY (ROE) DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BEI PERIODE 2018 – 2021 - Vida Mega Pradita; Dedi Suselo (Bajang Institute, 2022)
The stock price is one of the benchmarks or a sign of a company's financial stability, with a stable stock price it will also make a company still trusted by the public. The purpose of this study is to explore the factors that can affect the stock price of mining companies listed on the IDX during the 2018-2021 period, especially in financial ratios in the form of Return On Assets, Return On Equity and Debt to Equity Ratio of mining companies. An associative quantitative approach is the choice in this study, using panel data regression analysis. The results of the study show shares in mining companies. Then the Simultaneous F test shows that all variables Return On Assets, Return On Equity and Debt to Equity Ratio simultaneously have a significant effect on stock prices in mining companies. The conclusion in this study, it is important for companies to consider many factors in maintaining stock price stability, as an effort to maintain the company's existence in maintaining public trust as users or consumers.